Effect of Kangaroo mother care on physiological parameters in low birth weight neonates - Ranjan, Ankit; Malik, Sushma (International Journal of Contemporary Pediatrics, 2019)
Background: Low birth weight (LBW) babies require special care as they suffer from several handicaps, including maintenance of temperature, feeding, adequate weight gain and optimum neurobehavioral adaptation to the external environment. Kangaroo mother care (KMC) is an important modality that helps in the easy transition of the newborn infant to the outside world and overcomes the above problems. This study was planned to assess the effect of KMC on physiological parameters of low birth weight neonates, in a tertiary care hospital. Methods: This was a single-centered prospective observational quasi-experimental study conducted over a period of 18 months on 70 eligible LBW neonates. The arterial oxygen saturation, blood pressure (systolic, diastolic and mean), heart rate and respiratory rate of the neonates were noted. The readings at 1 hour and 2 hours after KMC were compared with that of the reading at 10 minutes prior to initiating KMC to assess the changes in the mentioned physiological parameters. Results: Analysis suggested statistically significant improvement in the arterial oxygen saturation and stabilization of the systolic, diastolic and mean blood pressure, heart rate and respiratory rate with institution of KMC. There was better improvement in the physiological parameters on increasing the duration of KMC from one hour to two hours and these changes were statistically significant. Conclusions: LBW neonates receiving KMC showed significant improvement in oxygen saturation and blood pressure, heart rate and respiratory rate.